Potential of Soursop Leaf Extract as an Antioxidant in MCF-7 Cells - Mustofa, Muhammad Samsul; Hadi, Restu Syamsul; Rahmah, Nunung Ainur; Pendrianto, Pendrianto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
The frequency of breast cancer tends to increase. Malondialdehyde (MDA) is a marker of oxidative stress as an end product from the chain reaction of lipid peroxidation. The use of traditional medicine soursopleaf (Annona muricata L.) has been reported for a long time because of its bioactivity as an antioxidant. This study analyzes the relationship between MDA levels and glutathione enzymes in MCF-7 cells given the methanol extract of soursop leaves. The methanol extract of soursop leaves was carried out by infusion method. The methanol extract of soursop leaves was given to cancer cells at several doses with an incubation of 24 hours. The cytotoxic test was carried out using the MTT method. Measurement of MDA levels was carried out using the thiobarbituric acid reactive substance (TBARS/TBA) reactivity test method. GSH measurements used the colorimetric method. The results showed that the ethanol extracts of soursop leaves have cytotoxic activity in the MCF-7 breast cancer cell line with IC50 values of 23.96 ppm. Ethanol extract of soursop leaves increased levels of MDA inhibition and GSH level. Soursop leaf extract could increase MDA inhibition GSH level in human breast cancer cells MCF-7.